Solve the following equation for A : 2A/3 = 8 + 4A
2a^3=8+4a2a^3-4a-8=0 a^3-2a-4=0 It occurred to me just now by looking at the equation that a=2 would work. And it does. So that's your answer.
2a/3=8+4a2a=3(8+4a) 2a=24+12a -10a=24 a=-24/10 a=-12/5
4a - 2.1 = 9a + 5.4 4a - 9a = 5.4 +2.1 -5a = 7.5 -a = 1.5 a = -1.5
8a+4a=144 12a=144 12a/12=144/12 A=144
4a - 5b = 74a +5b = 17From the first equation:4a = 7 + 5bsubstitute this value in the second equation:7 + 5b + 5b = 177 + 10b = 1710b = 10b = 1Now,solve for a :4a - 5(1) = 74a = 7 + 54a = 12a = 3
a + 4 = 10(a + 4) - 4 = 10 - 4a = 6
Add the equations: 4a + 4a - 5b + 5b = 7 + 17 ie 8a = 24 a = 3, so b = 1
4a - 9 = 27 4a = 36 a = 9
-4a = 48 a = -12
Without an inequality sign it can't be considered to be an equation but it can be simplified to: 4-2a
a-16 = a/4+2 Multiply all terms by 4: 4a-64 = a+8 4a-a = 8+64 3a = 72 a = 24
9=4a+13 9-13=4a -4=4a -4/4=a -1=a a=-1
4a + a = 25 add 4a and a 5a = 25 then divide 25 by 5 a = 5
The general equation of a parabola is y = ax2 + bx + c.The vertex of a parabola is (-b/2a, c - b2/4a). In our case the vertex is (2, -4). So we have,-b/2a = 2, so that b = -4a, andc - b2/4a = -4 (substitute -4a for b)c - (-4a)2/4a = -4c = 16a2/4a = -4 (simplify)c - 4a = -4 (solve for c)c = 4a - 4By substituting -4a for b, and 4a - 4 for c, the equation becomes,y = ax2 + bx + cy = ax2 + (-4a)x + 4a - 4Since it is given that when x = -3, y = -3, we substitute them into the new equation and solve it for a. So we have,y = ax2 + (-4a)x + 4a - 4-3 = a(-3)2 + (-4a)(-3) + 4a - 4-3 = 9a + 12a + 4a - 4 (add 4 to both side, and add alike terms on the right-hand side)1 = 25a (divide by 25 to both sides)1/25 = a (this is the required answer)If you want to find the equation of the parabola, just substitute 1/25 for a, such as:y = ax2 + (-4a)x + 4a - 4y = (1/25)x2 + [-4(1/25)]x + 4(1/25) - 4y = (1/25)x2 -4/25x + 4/25 - 4y = (1/25)x2 -4/25x + 96/25
It is an equation and the value of a is 7
The GCF is 4a. The equation factors into 4a(5a + 9)
Because of limitations with the question software, some symbols cannot be rendered, so we don't know what operation there is between the 5a and the 4a-1. Assuming a plus sign produces an inconsistent equation. But if we assume a / (slash) for division, we get a quadratic equation that produces some reasonable roots, so here's what I think the question is: Can you solve the following equation for a: 5a/(4a-1) = 9a-4 ? Yes you can! Multiply both sides of the equation by 4a-1. This gives you: 5a = (9a-4)(4a-1) Expand the right side, which gives you 5a = 36a2 -9a -16a + 4 Subtract 5a from both sides and group similar terms: 0 = 36a2 -30a + 4 Now, use the quadratic formula to solve for a(left to the student): a1 = 2/3; a2 = 1/6
It can't be an equation, there is no sign of equality.
9a + 4a = 26 13a = 26 a = 26/13 a = 2
4a-2=7a-6 4=3a a=4/3
5a - 10 = 4a + 8 is a linear equation in one variable.
11a+9 = 4a+30 11a-4a = 30-9 7a = 21 Solution: a = 3
4a + 6 - 4a = -10 Combining like terms: 6 = -10 or 4 = 0 which is FALSE. So the solution set is empty.
If you mean: 4a-3 = 2a+7 then the value of a works out as 5